2018
DOI: 10.1542/peds.2018-0115
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Neonatal Antibiotic Use

Abstract: OBJECTIVES: We sought to identify whether and how the NICU antibiotic use rate (AUR), clinical correlates, and practice variation changed between 2013 and 2016 and attempted to identify AUR ranges that are consistent with objectively determined bacterial and/or fungal disease burdens. METHODS: In a retrospective cohort study of >54000 neonates annually at >130 California NICUs from 2013 to 2016, we computed nonparametric linear correlation and compared AURs among years using a 2-sample test of proportions. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 19 publications
3
48
1
1
Order By: Relevance
“…Antibiotic treatment decreases gut microbial diversity and enriches for AR potential pathogens [54]. Antibiotics delivered in the NICU are varied, [63] ranging from relatively shortterm exposure with narrow-spectrum agents such as ampicillin or cefazolin to long-term exposure with broad-spectrum agents such as 3rd-generation cephalosporins and carbapenems [54,64]. The preterm gut microbiota of NICU-hospitalized neonates is dominated by Escherichia coli, Klebsiella spp., Enterobacter spp., and Enterococcus spp., which are found in the NICU environment, are often multi-drug resistant, and are causes of bacteremia in this population [54,65,66] ( Table 2).…”
Section: Vulnerable Infancymentioning
confidence: 99%
“…Antibiotic treatment decreases gut microbial diversity and enriches for AR potential pathogens [54]. Antibiotics delivered in the NICU are varied, [63] ranging from relatively shortterm exposure with narrow-spectrum agents such as ampicillin or cefazolin to long-term exposure with broad-spectrum agents such as 3rd-generation cephalosporins and carbapenems [54,64]. The preterm gut microbiota of NICU-hospitalized neonates is dominated by Escherichia coli, Klebsiella spp., Enterobacter spp., and Enterococcus spp., which are found in the NICU environment, are often multi-drug resistant, and are causes of bacteremia in this population [54,65,66] ( Table 2).…”
Section: Vulnerable Infancymentioning
confidence: 99%
“…Decreases in overall neonatal antibiotic utilisation are reported in conjunction with multiple antimicrobial stewardship interventions25–27 and among term infants with use of multivariate risk models for EOS risk assessment 28 29. Schulman et al recently reported a significant decrease in antibiotic use rate of 21.9% in ~130 NICUs across California from 2013 to 2 016 30. They found a greater reduction in centres participating in study-defined antibiotic stewardship efforts compared with centres without such participation (28.7% vs 16.2%) underscoring the importance of stewardship efforts.…”
Section: Drivers Of Antibiotic Use and Opportunities For Antibiotic Smentioning
confidence: 99%
“…A final use of biomarkers may be to determine length of therapy for conditions in which antibiotic use in mandated. Hemels et al 59 observed that most CONS bacteraemia at their centre resolved within 72 hours of antibiotic initiation when the infants demonstrated clinical improvement, CRP levels decreased and central catheters were removed 30. This group later reported an observational experience of treating infants meeting such criteria with 3 or 7 days of antibiotics, and found no difference in resolution of bacteraemia or clinical outcome 59.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%
“…The use of chloramphenicol with the associated grey baby syndrome is a historical illustration of potentially relevant toxicity, while inadequate dosing may result in therapeutic failure. Off-label use has the potential to result in inadequate or inaccurate dosing and explains the variations in dosing regimens for antibiotics in both US as well as European neonatal intensive care units [19,20].…”
Section: Approaches When Adult And/or Pediatric Dosing Is Available Amentioning
confidence: 99%